Bananas/les bananes - International Network for the Improvement of Banana and Plantain (2000)
There are more than a thousand varieties of banana, the tallest herb in the world. This document traces the history of the nutritious fruit which is one of the most important food crops in the world. The dessert banana industry is described. The crop management cycle is presented from planting to harvest and particular attention is paid to crop protection. This public awareness publication includes numerous illustrations. Provided as a set together with a multimedia CD-Rom